Construction of rutile/anatase TiO2 homojunction and metal-support interaction in Au/TiO2 for visible photocatalytic water splitting and degradation of methylene blue. (8th January 2023) - Yu, Huanhuan; Li, Siyuan; Peng, Siyan; Yu, Zhongliang; Chen, Fayun; Liu, Xiaotong; Guo, Jiuli; Zhu, Baolin; Huang, Weiping; Zhang, Shoumin
Abstract: Homojunction structure could present synergetic effect of an enhanced charge transfer and decreasing the electron-hole recombination. In this investigation, rutile/anatase TiO2 homojunction was prepared by sol-gel synthesis with nitric acid (HNO3 ) as peptizing agent. Au/TiO2 was prepared by photoreduction deposition process. The photocatalytic performance for water splitting and the degradation of methylene blue (MB) was evaluated. 1% Au/TiO2 -HNO3 possessed good photocatalytic activity with hydrogen evolution rate of 8.77 mmol/h/g, and MB degradation efficiency of about 69.70% under visible light irradiation. The results indicated TiO2 -HNO3 conceived optimum composition ratio of rutile and anatase phases to construct the homojunction structure enhancing charge transfer and decreasing the electron-hole recombination favorable for photocatalytic performance. Further, the strong metal-support interaction as well as the localized surface plasmon resonance (LSPR) of Au species accounted for the results of Au/TiO2 especially Au/TiO2 -HNO3 possessing higher hydrogen evolution and degradation of MB performance than TiO2 . Graphical abstract: Image 1 Highlights: Rutile/anatase TiO2 homojunction was prepared by facile sol-gel method. Rutile/anatase TiO2 homojunction achieved effective long-range charge separation. Band gap narrowing can be achieved using homojunction. Homojunction effect and metal-support interaction well improve photocatalytic performance.